Cytoreductive surgery and hyperthermic intra‐peritoneal chemotherapy treatment of colorectal peritoneal metastases: Cohort analysis of high volume disease and cure rate. Issue 2 (21st May 2014) - Cashin, Peter H; Dranichnikov, Faoz; Mahteme, Haile
<x xml:space="preserve">Abstract</x> Background Cytoreductive surgery (CRS) and hyperthermic intra‐peritoneal chemotherapy (HIPEC) treatment of colorectal peritoneal metastases (PM) is an established treatment alternative. The study aim was, first, to investigate the outcome of high‐volume disease defined by the peritoneal cancer index (PCI) 20; second, to report the long‐term disease‐free survival of patients with >5 years observation. Methods Consecutive patients with colorectal PM from a prospective HIPEC database between 2004 and 2010 were included, 67 patients. Clinicopathological and outcome parameters were compared between low PCI (n = 40) and high PCI (n = 27). A subgroup analysis on patients with >5 years observation was performed (n = 32). Disease‐free survival after 5 years defined cure. Results Median overall survival (OS) was 28 months, low PCI‐group 33 months versus high PCI‐group 17 months (P = 0.03). Median OS of patients with complete CRS (n = 56) was 30 months, low PCI‐group 37 months versus high PCI‐group 27 months (P = 0.2), with 5‐year survival of 31% and 21%, respectively. No difference in morbidity/mortality. The cure rate was 22% in the subgroup (7/32) and 28% in those with complete CRS (7/25). Two patients in the cured group had PCI 29 and 34. Discussion Treatment of high‐volume disease may result in long‐term survival and even cure. The key is to reach a complete CRS. The overall cure rate is 22%. J. Surg. Oncol. 2014; 110:203–206. © 2014 Wiley Periodicals, Inc.